Associations of maternal pre-pregnancy body mass index and gestational weight gain with risk of offspring neurodevelopment at 2 years: A Chinese birth cohort study - Dong, Xiaohan; Zhou, Aifen (Frontiers in Pediatrics, 2023)
Introduction In recent decades, there has been a surge in both obesity and developmental impairments. Only a few research have looked at the relationship between gestational weight growth and pre-pregnancy BMI in mothers and the neurobehavioral development of their infants. The current research investigates the associations among maternal pre-pregnancy BMI, GWG, and the risk of child neural development at 2 years of age depending on a Chinese birth prospective study. Methods The study population was 3,115 mother-infant pairs were registered in the Wuhan Health Baby cohort between September 2013 and October 2018, and data from this cohort was used in this investigation. The Chinese classification was used to group maternal BMI before conception. Based on the 2019 Life Cycle Project-Maternal Obesity and Childhood Outcomes Study Group, categories for GWG were created. The outcome was an assessment of child neural development at age 2 which was measured by employing a Chinese translation of the Bayley scales (BSID-CR). The multivariate regression models were used to calculate the beta (β) coefficients and 95% confidence intervals (CIs) for estimating the associations between continuous Bayley scores and maternal pre-pregnancy BMI categories, as same as in GWG categories. Results Infants of overweight and obese moms exhibited lower MDI scores than those of mothers with normal pre-pregnancy BMI (β = −2.510, 95%CI = −4.821 to −0.200) in the entire sample. Meanwhile, we find among the normal pre-pregnancy BMI mothers, infants of inadequate GWG mothers had lower MDI scores (β = −3.952, 95%CI = −7.809 to −0.094) compared with the referenced adequate GWG mothers, as well as the infants of excessive GWG mothers among the underweight pre-pregnancy BMI mothers (β = −5.173, 95%CI = −9.803 to −0.543). The PDI scores of the infants were not affected by the maternal pre-pregnancy BMI or GWG. Conclusion For Chinese babies aged 2 in this nationally representative sample, aberrant pre-pregnancy BMI and GWG can impair infants’ mental development, but not psychomotor development. Such results are significant given the incidence of overweight and obesity as well as the long-term effects of early brain development. In this study we found optimal GWG recommendations proposed by 2019 Life Cycle Project-Maternal Obesity and Childhood Outcomes Study Group were more suitable for Chinese women than 2009 Institute of Medicine(IOM) guidelines. Additionally, women should be given general advice on how to achieve their ideal pre-pregnancy BMI and GWG.